2011
DOI: 10.1016/j.molimm.2011.02.008
|View full text |Cite
|
Sign up to set email alerts
|

2B4 utilizes ITAM-containing receptor complexes to initiate intracellular signaling and cytolysis

Abstract: 2B4 is a member of the SLAM receptor family capable of activating NK cell cytotoxicity in the context of EBV infection. SAP (SLAM Associated Protein) deficiency causes defective signaling downstream of SLAM family receptors and high susceptibility to EBV. 2B4 costimulates natural cytotoxicity receptor (NCR) and TCR initiated signals to induce cellular cytotoxicity and cytokine release. The 2B4-SAP signal transduction pathway is not predicted to overlap with the TCR-ITAM pathway, although SAP is required for so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Stimulation of PBLs with anti-CD3 antibody alone did not significantly affect DGKα activity (data not shown). Since activation of SLAM family receptors was reported to enhance TCR signaling (28, 29), we investigated whether SLAM might regulate the enzymatic activity of DGKα. Indeed, 15 min of co-stimulation of PBLs with anti-CD3 and anti-SLAM agonist antibodies resulted in an even stronger inhibition of DGKα activity without affecting DGKα protein content (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation of PBLs with anti-CD3 antibody alone did not significantly affect DGKα activity (data not shown). Since activation of SLAM family receptors was reported to enhance TCR signaling (28, 29), we investigated whether SLAM might regulate the enzymatic activity of DGKα. Indeed, 15 min of co-stimulation of PBLs with anti-CD3 and anti-SLAM agonist antibodies resulted in an even stronger inhibition of DGKα activity without affecting DGKα protein content (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SAP is essential for SLAM tyrosine phosphorylation by recruiting the Src-related kinase FynT (3, 34), however, a growing body of evidence indicates that SAP is also involved in T cell responses to antigenic stimulation (2). Indeed SAP binds directly to ITAM sequences of CD3ζ subunit (29), while TCR activation promotes the recruitment of SAP and SLAM family receptors to the signalosome (28, 29, 49). Furthermore, genetic deletion of SAP in mice results in the impairment of TCR/CD28-induced DAG-mediated activation of PKCθ and of downstream signaling events (7).…”
Section: Discussionmentioning
confidence: 99%
“…2F). While previous findings on the association of CD3ζ with CD244 [22] may partially account for these results, the nature of the effect on CD160 remains to be investigated.…”
Section: Expression Of a Functional Tcr Complex On The Cell Surface Omentioning
confidence: 90%
“…Although we do not know whether CD3 co-engagement leads to the same patterns of phosphorylation of Ly108 tyrosine motifs, such potentiation of Ly108 signaling by TCR stimulation could also be envisioned if the signaling pathways of these two receptors intersect. Recently, it was reported that 2B4 can utilize ITAM motif-containing proteins to influence signaling in NK cells (53). It will be of interest to see whether Ly108 intersects with TCR signaling pathways to cause synergistic downstream effects.…”
Section: Discussionmentioning
confidence: 99%